Language hybridity among Nepali Twitter users: Trend and possible implications - Bhandari, Ganga Laxmi (Journal of NELTA, 2019)
In Nepal, Twitter has recently been one of the fastest means of communication and information sharing app. This social networking site is used to express ideas, communicate messages, dispute opinions and expression of others and vent frustrations. What is striking is the use of hybridity or bilingualism in tweets in which Nepali and English are used freely and almost inseparably not just in chitchats but also in communicating information of public importance. Curious to see if such ybridity has the potential to contribute to changing perspectives on teaching and learning English, a brief study was undertaken in November-December 2018 as wells in June 2019. The study included selection of random tweets within the specific period of time and their analysis in terms of the currency and diversity of opinions expressed. The results show that hybridity is popular among Nepali tweeters not just in casual expressions, but also in serious communications, such as in formal complaints/notices, advertisements and commentaries on issues of public concern. The result also indicates that the ELT community cannot remain aloof of the language pattern.